Hairy Cell Leukemia with Unusual Loss of CD103 in a Subset of the Neoplastic Population: Immunophenotypic and Cell Cycle Analysis by Flow Cytometry - Yuan, Constance M (e-Century Publishing Corporation, 2008)
We report an unusual case of hairy cell leukemia (HCL) in a 55-year-old male who presented with fatigue, increased bruising, leukocytosis, anemia, thrombocytopenia and moderate splenomegaly without lymphadenopathy. Microscopically, a monomorphic population of small to medium-sized lymphoid cells with bean-shaped nuclei, ground glass chromatin and fine cytoplasmic projections was identified in the peripheral blood and bone marrow. Flow cytometric immunophenotyping demonstrated a monoclonal population of mature B cells with coexpression of CD25, CD11c and CD103. The clonal B-cells all exhibited homogenous expression of CD20 and uniform light scatter characteristics. However, CD103 expression was present in only half of the clonal B-cells. Flow cytometric cell cycle analysis using DRAQ5 DNA dye in intact live cells showed that both the CD103-positive and CD103-negative cell subsets exhibited a low S-phase fraction with no significant difference between the two subpopulations. Clinical remission was achieved by treatment with 2-chlorodeoxyadenosine. Variant and atypical cases of HCL have been described with varying intensity of CD11c, loss of CD25, aberrant expression of CD10, and lack of CD103 expression. However, the lack of CD103 in only a subset of the malignant cells in our case is an immunophenotypic aberrance that, to our knowledge, has not been previously reported.